2016
DOI: 10.1038/ctg.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in African Americans: An Update

Abstract: This review is an update to the American College of Gastroenterology (ACG) Committee on Minority Affairs and Cultural Diversity's paper on colorectal cancer (CRC) in African Americans published in 2005. Over the past 10 years, the incidence and mortality rates of CRC in the United States has steadily declined. However, reductions have been strikingly much slower among African Americans who continue to have the highest rate of mortality and lowest survival when compared with all other racial groups. The reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 81 publications
7
75
1
Order By: Relevance
“…This may well be a trend that will be seen in the UK. Improved cancer survival rates are seen in the under 40 age group, and are enhanced further if they are physically fit [1,9,11]. This corresponded with the findings in this study, which demonstrated the median and overall survival rate for the under 40 age group to be 94.7 months and 67.4% respectively.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This may well be a trend that will be seen in the UK. Improved cancer survival rates are seen in the under 40 age group, and are enhanced further if they are physically fit [1,9,11]. This corresponded with the findings in this study, which demonstrated the median and overall survival rate for the under 40 age group to be 94.7 months and 67.4% respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Like all cancers, colorectal cancer remains a multi-factorial disease with multiple risk factors, such as lifestyle choices (particularly exercise, diet and weight) and access to healthcare, each playing a role [1,9,11,17]. The results outlined above suggest that age, gender, ethnicity and tumour site may be implicated in determining prognosis, specifically with regard to survival rates.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Relative to other races, African Americans have lower screening rates for CRC, higher incidence rates, earlier mean age at onset, worse survival and late-stage presentation, and a higher proportion of cancers before age 50 (140)(141)(142)(143). Th ese various eff ects result from both socioeconomic and biologic factors ( 144 ).…”
Section: Resultsmentioning
confidence: 99%